LALITHAMBIKA ANTHARJANAM’S REACTION AGAINST THE CONCEPT OF “ANTHARJANAM” IN AGNISAKSHI: LIFE OF THETHI - ANIL, INDU C; CHELLIRIAN, B. SONIA (International Journal of Psychosocial Rehabilitation, 2020)
Agnisakshi (Fire, My Witness), the only novel of Kerala’s eminent women writers, Lalithambika Antharjanam which tells an account of a Namboothiri woman called Thethikutty, who got liberated from the confines of her homes and left her family for the eternal fulfilment. Lalithambika Antharjanam encountered almost all the incidents from her own life experiences, especially the way she treated in her Illom. The story of Agnisakshi centers the deep and blind caste system and the practice of patriarchy of a Namboothiri household, which reveals the world of Namboothiri men and their rules and rituals which always avoided women from everywhere near their works. Thethikutty, the heroine of the novel tries to battle with these traditional norms which she prohibited from all the pleasures and happiness of her life, especially after she got married off to Unni Namboothiri the one who’s not a typical orthodox husband, but the one who grown up in those old systems.Thethi encountered with many obstacles to find out the real freedom, and she received the path of renunciation, the way she wanted to really live. There she found freedom and relief in every aspect especially breaking away all the rules and regulations of a typical Namboothiri women who’s basically called ‘Antharjanam’ the one who is inside or ‘Akathullol.’ In sum, the whole paper is going to scrutinize the system of ‘Antharajanam’ and how it is established in the novel Agnisakshi which is written by Lalithambika Antharjanam by looking deeply into the life of Thethikutty.